Secondary Trading Costs in the Municipal Bond Market - HARRIS, LAWRENCE E.; PIWOWAR, MICHAEL S. (Journal of Finance, 2006)
ABSTRACT Using new econometric methods, we separately estimate average transaction costs for over 167,000 bonds from a 1‐year sample of all U.S. municipal bond trades. Municipal bond transaction costs decrease with trade size and do not depend significantly on trade frequency. Also, municipal bond trades are substantially more expensive than similar‐sized equity trades. We attribute these results to the lack of bond market price transparency. Additional cross‐sectional analyses show that bond trading costs increase with credit risk, instrument complexity, time to maturity, and time since issuance. Investors, and perhaps ultimately issuers, might benefit if issuers issued simpler bonds.